Government Strategy In Market Service Retribution Through E-Nyank System: Strategi Pemerintah Dalam Retribusi Pelayanan Pasar Melalui Sistem E-Nyank - Mawaddah Warohma, Ayu; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2022)
Regional autonomy gives authority to districts or cities to regulate each district or city individually. Regional autonomy has been officially enacted since January 1, 2001. It is hoped that the implementation of autonomy will allow districts to be more creative in obtaining individual local revenues and financing district outputs in running the government. Implementation of the Government's Strategy in Market Service Retribution Through the E-Nyank System at Gedangan Market, Sidoarjo Regency cannot be separated from obstacles. The problem of implementing the program strategy is, first, the lack of a retribution checking officer in checking retribution payments, so that they are less effective in carrying out their duties. Second, the human resources at Gedangan Market who don't want to bother using smartphones and top-up balances. This study aims to analyze the Government's Strategy in Market Service Retribution through the E-Nyank System at Gedangan Market, Sidoarjo Regency. The type of research used is descriptive qualitative. Data collection techniques were carried out through observation, interviews and documentation. Determination of informants using purposive sampling technique. The data analysis technique was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that the Government's Strategy in Market Service Retribution is not yet optimal through the E-Nyank System at Gedangan Market, Sidoarjo Regency marked by the unfulfilled indicators in the strategy process according to Kooten in Salusus (2006:104-105), namely organizational strategy indicators, program strategy, resource support strategy and institutional strategy.